COMPETENCY: DEVELOPMENT, INTEGRATION, AND APPLICATION - Steven Moulton; Oki Sunardi; Gino Ambrosini (Universitas Bunda Mulia, 2017)
Many companies and organizations are increasingly focusing on human capital as a competitive advantage in a rapidly changing environment. To achieve business success, companies are expecting their employees to perform at higher levels, to be more customer-responsive, more process-oriented, more involved in shared leadership and more responsible for creating the knowledge that adds value to an organization’s distinguishing capabilities. When embarking on the path of selecting and defining competencies, an organization needs to pause for an introspective review. Linking competencies to the organization’s purpose, goals and values is the key to positively affect the organization’s direction and bottom line. Competencies can be categorized into one of four groups, organization-based, individual-based, technical and behavioral. From a strategic direction approach, the organization that knows and understands its core competencies and capabilities can use them to attain a strategic advantage. In addition, the organization understands that there is a diverse cross section of organizational competencies that are necessary for fulfilling its mission. Successful application of competencies lies in how they are defined. Simplicity and measurability are keys for competencies to be accepted and measured throughout an organization.Keywords: competencies, core competencies, organizational competencies, simplicity and measurability